Gastrointestinal Dysfunction after Traumatic Brain Injury: Mechanisms Linking The Gut, Inflammation, and the HPA Axis - Dwi Hastuti; A Jusman, Sri Widia; Reni Paramita (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Traumatic brain injury (TBI) is a major global health problem that often leads to systemic complications beyond neurological damage, notably gastrointestinal (GI) dysfunction. The mechanisms linking TBI to GI complications remain inconclusive. We conducted a systematic review using current clinical evidence on the pathophysiological processes underlying post-TBI GI dysfunction, focusing on two principal mechanisms: inflammatory-oxidative processes and hypothalamic–pituitary–adrenal (HPA) axis alterations. A comprehensive search was conducted through PubMed, Cochrane Library, and Scopus to identify eligible studies. Evidence indicates that surges of proinflammatory mediators and chemokines, along with reduced anti-inflammatory mediators, drive systemic immune imbalance. Moreover, iNOS upregulation and gut microbiota dysbiosis contribute to mucosal injury. Concurrently, HPA axis dysregulation exerts a bidirectional impact. Elevated ACTH and cortisol reflect an intact stress response that may stabilise metabolism if combined with early enteral nutrition, whereas critical illness-related corticosteroid insufficiency (CIRCI) and hypergastrinemia are strongly associated with gastrointestinal bleeding and mortality. Together, these findings underscore the synergistic role of inflammatory and endocrine disturbances in driving gastrointestinal vulnerability after TBI. Understanding these mechanisms is crucial for developing biomarker-based monitoring and targeted interventions to improve prognosis and reduce GI-related complications in TBI patients.